The multiplicity of causes according to the fundamentalists and its impact on the differences of jurists - usury is an example - - Mohsen Hayjan Abdullah, (Islamic Sciences Journal, 2024)
ABSTRACT The multiplicity of causes according to the fundamentalists is one of the reasons for disagreement among jurists, and this appears in the cause of usury, where jurists have differed on several opinions. Therefore, after the introduction, the research topic will include two sections. The first section includes the definition of the reason, its parts, conditions, paths, and the multiplicity of reasons, in five topics. The second section includes the concept of usury, the sayings of scholars and their evidence regarding the usurious reason, and a discussion of the evidence and weighting, in five topics, and the conclusion, which includes The results reached during the research